THE EFFECT OF SERVICE QUALITY, INFORMATION TECHNOLOGY UTILIZATION, AND CUSTOMER VALUE ON CUSTOMER SATISFACTION AND ITS IMPACT ON CUSTOMER LOYALTY - Syaputra, Eka; Soviyanti, Efrita; Nofrizal, Nofrizal (Jurnal Daya Saing, 2026)
This study aims to analyze the effects of service quality, information technology utilization, and customer value on customer satisfaction and their impact on customer loyalty at the Industrial Standardization and Service Center (BSPJI) Pekanbaru. This research employs a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through a structured questionnaire distributed to 226 BSPJI customers selected using purposive sampling. The results indicate that service quality, information technology utilization, and customer value have positive and significant effects on customer satisfaction. Furthermore, customer satisfaction has a significant positive effect on customer loyalty. Mediation analysis reveals that customer satisfaction significantly mediates the relationship between service quality, information technology utilization, customer value, and customer loyalty. These findings highlight the critical role of customer satisfaction as a key mechanism in building customer loyalty. Therefore, BSPJI Pekanbaru should prioritize improving service quality, optimizing information technology utilization, and enhancing customer value to strengthen customer satisfaction and long-term loyalty